APLIKASI PENDATAAN KADER PADA DPD KOMITE NASIONAL PEMUDA INDONESIA (KNPI) ACEH - Muammar; Salam, Abdus; Fathurrahmad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2022)
As a DPD organization the Indonesian National Youth Committee (KNPI) Aceh Province requires an information system to improve performance in this organization. In the member data processing system and cadre identity index in the DPD Indonesian Youth National Committee (KNPI) Aceh Province, all data is stored in spreadsheet worksheets. The process of organizing data between regions and commissariats certainly has a relationship with each other, so that in urgent situations it is possible to have difficulties in organizing member data due to different data formats, different reporting formats, and searching for member information which is difficult because it is still manual, it is necessary an application that can store and organize data so that it is easily accessible by cadres/members. Seeing these problems, the authors want to develop a web-based membership information system that allows users to maintain, renew, maintain alignment of data collection formats, report and find member information easily and quickly. The system development method that the author uses is Rapid Application Development (RAD). In the end, it is hoped that this system will provide convenience in organizing member data effectively and efficiently. The results of the research are the availability of applications that can be used to process data on cadre members in the DPD KNPI Aceh Province and used as an alternative tool for processing data on cadre members in the DPD KNPI Aceh Province.